Design and Implementation of Web-Based Dynamic Mathematics Intelligence Education Platform - Guan, Hao; Rao, Yongsheng; Wang, Ying; Li, Xiaoxia; Chen, Ruxian (2018 7th International Conference on Digital Home (ICDH), 2018)
The information and communications technology (ICT) in education can effectively promote the development of ICT in subject by going to depth of a subject, and can practically assist a teaching process and improve the teaching quality. A dynamic mathematics intelligence education platform (DMIEP) is a tool of ICT in subject that goes to the depth of the mathematics subject. This thesis briefly reviews the development of the web-based dynamic mathematics software; proposes that design principles of the web-based, especially a mobile internet-based, DMIEP software should be "opening and sharing"; and provides goals to be achieved, such as seamless integration with a system or a third party application in a cross-terminal manner, good expansibility, and intelligence. Under the guidance of the principles and goals, an opening and sharing DMIEP has been designed and implemented, having functions such as relationship-based drawing, geometric graphic transformation, dynamic measurement, dynamics and parameters iteration, geometrical theorem automatic reasoning, and opening interfaces. At present, the platform has been widely used in the mathematics teaching process of primary and secondary schools.